Pamięć gatunków Ponowoczesne dylematy atrybucji gatunkowej - Grochowski, Grzegorz (Nowa Humanistyka, 2018)
The monograph by Grzegorz Grochowski documents insightful reflection on the current state of the field of the genre order of discourse, especially literary taxonomies. These orders are seen from the perspective of various methodological orders of the last few decades, developed in the area of postmodern literary studies. The conclusions emerging from these are examined from the angle of analytical utility of selected solutions. The study is successful at depicting the current state of the debates on the theory of literature and the dynamics of phenomena observed in the field of contemporary literature. It combines an in-depth theoretical analysis with sophisticated interpretations of the texts. Therefore, it skilfully transports theoretical discussions on to a concrete level. (excerpt from a review by Prof. Teresa Dobrzyńska) The fascinating book by Grzegorz Grochowski on the postmodern literary games is also a game the researcher plays with traditional genology and the aim of creating categories other than genre and text for this literary play: those of description and understanding. Discourse analysis leads theory of literature out of the narrow backwater of literary theories. It also demonstrates that literature has a meaning not only against the backdrop of language and genological norm, that its dynamics require a return into the chaos of social life (rejected by structuralism). (excerpt of a review by Prof. Zofia Mitosek)